Challenging diagnostic and therapeutic modalities for leiomyosarcoma of inferior vena cava. (January 2015) - Mastoraki, Aikaterini; Leotsakos, George; Mastoraki, Sotiria; Papanikolaou, Ioannis S.; Danias, Nikolaos; Smyrniotis, Vasilios; Arkadopoulos, Nikolaos
Abstract: Leiomyosarcoma of the inferior vena cava (IVCL) is a rare malignant tumour originating from the smooth muscle cells of the media with intra- or extra-luminal growth. The type of the lesion is further divided into three levels in relation to hepatic and renal veins respectively. The aim of this review was to evaluate the results of surgical treatment of IVCL with special reference to the extent of its histological spread and to analyse the recent literature in order to provide an update on the current concepts of diagnostic and therapeutic management of this entity. IVCL's patients may present with non-specific complaints such as dyspnoea, malaise, weight loss, nausea, vomiting, fever and abdominal pain. Haematogenous metastasis is frequent. At a later stage, IVCL may also spread through lymphatic. Multiple diagnostic imaging techniques have been proposed for accurate preoperative diagnosis, including Doppler ultrasonography (US), computed tomography (CT) and magnetic resonance imaging (MRI), individually or in combination with cavography echocardiography or CT-guided biopsy. Despite recent research on the therapeutic strategies against IVCL, surgical resection appears the only potentially curative approach. Unfortunately, a mere minority of patients is eligible to undergo surgical intervention. In addition, surgical removal of IVCL does not necessarily guarantee patient's long-term survival. Alternative therapies, such as radio- and chemo-therapy often proved insufficient. Debate continues regarding the optimal management of the IVC after tumour resection, with primary repair, ligation and IVC reconstruction all have been utilized with varying success. Highlights: Leiomyosarcoma of the inferior vena cava (IVCL) is a rare malignant tumour. The type of the lesion is further divided into three levels. Surgical resection appears the only potentially curative approach. Debate continues regarding the optimal management of the IVC after tumour resection. Primary repair, ligation and IVC reconstruction have been proposed.